Book Review "Glonggong", Junaidi Setiyono, Serambi Ilmu Semesta, Jakarta, ISBN 978-979-1275-48-4 - Mafazi, Sarwan Saukhi (Semarang State University Undergraduate Law and Society Review, 2021)
This book tells about a young man of noble descent who lived a simple life and lived among the poor during the struggle of Prince Antawirya or better known as Prince Diponegoro in Central Java. The Java War or De Java Oorlog (Netherlands) was a major and comprehensive war that lasted for five years (1825-1830) which took place in Java, between the Dutch colonial forces under the leadership of General De Kock against the indigenous population led by a Yogyakarta prince named Prince Diponegoro. or who in this novel is referred to as Kangjeng Sultan Ngabdulkamid. This war was one of the biggest battles experienced by the Dutch during colonizing the archipelago. Where the victims of this war reached two hundred thousand more dead. This war involved the entire Java region, so this war is called the Java War. However, this book does not explain in depth about the Javanese war and also does not explain the life or struggle of a hero like Prince Diponegoro, but this book tells the history from another person's point of view about the personal life of a young Dipanegaran laskar follower and the social conditions of society in the past. the Javanese battle.